Effect of cavity preparation design and ceramic type on the stress distribution, strain and fracture resistance of CAD/CAM onlays in molars (Journal of Applied Oral Science, 2022)
Objective: This study aimed to evaluate the effect of the cavity preparation and ceramic type on the stress distribution, tooth strain, fracture resistance and fracture mode of human molar teeth restored with onlays. Material and Methods: Forty-eight molars were divided into four groups (n=12) with assorted combinations of two study factors: BL- conventional onlay preparation with boxes made from leucite ceramic (IPS-Empress CAD, Ivoclar Vivadent); NBL- conservative onlay preparation without boxes made from leucite ceramic; BD- conventional onlay preparation with boxes made from lithium disilicate glass ceramic (IPS e.max CAD, Ivoclar Vivadent); NBL- conservative onlay preparation with boxes made from lithium disilicate glass ceramic cuspal deformation (µS) was measured at 100 N and at maximum fracture load using strain gauge. Fracture resistance (N) was measured using a compression test, and the fracture mode was recorded. Finite element analysis was used to evaluate the stress distribution by modified von Mises stress criteria. The tooth strain and fracture resistance data were analyzed using the Tukey test and two-way ANOVA, and the fracture mode was analyzed by the chi-square test (α=0.05). Results: The leucite ceramic resulted in higher tooth deformation at 100 N and lower tooth deformation at the maximum fracture load than the lithium disilicate ceramic (P<0.001). The lithium disilicate ceramic exhibited higher fracture resistance than the leucite ceramic (P<0.001). The conservative onlay resulted in higher fracture strength for lithium disilicate ceramic. Finite element analysis results showed the conventional cavity preparation resulted in higher stress concentration in the ceramic restoration and remaining tooth than the conservative onlay preparation. The conservative onlays exhibited increased fracture resistance, reduced stress concentration and more favorable fracture modes. Conclusion: Molars restored with lithium disilicate CAD-CAM ceramic onlays exhibited higher fracture resistance than molars restored with leucite CAD-CAM ceramic onlays.